Evaluation of Four Wheeled Vehicle Student Driver Adaption’s on Right & Left Steering Wheel Through the User Experience Approach - Maulida Hakim, Inaki; Pratama Putra, Ferdiansyah (International Journal of Engineering and Technology, 2018)
The high level of activity that people carry out daily encourage the need for high mobility in the fulfillment of these activities. Vehicles can help to ease people in doing activities so that one's activities can run effectively and efficiently. Every vehicle produced by a vehicle company has a difference in terms of features and systems that are in it, so it causes the vehicle users to have to adapt. In addition, there are other differences in driving position. So this study aims to evaluate the adaptation of four-wheeled vehicle student driver in Indonesia on the right-steering and left-steering vehicle through the user experience approach. This study focus on what factors can influence the adaptation of driver to vehicle differences and differences in driving position. Evaluation is done by giving task to the respondent at the beginning of the drive, during drive and at the end of the drive by looking at the safety factor on activity being done. The methods used are performance metrics, Single Ease Question (SEQ) questionnaire and Questionnaire for User Interface Satisfaction (QUIS). Based on results of the research, there are some errors and time used for respondents in adapting. So in an effort to correct from the error, additional information is given where the information can be useful in adapting.Â